'Murderer, Delinquent or Unemployed': Photojournalism and Visualizing the French Unemployed in the 1930s. Issue 2 (July 2019) - Perry, Matt
Abstract : This article examines the contribution of photography to the recognition of the unemployed during the 1930s. It focuses on the role of French photomagazines, most notably Vu and Regards. Providing a rich body of representations of the unemployed, these periodicals developed several strategies to render the unemployed visible and to distinguish them from other forms of poverty. Underlying the photomagazine's modernist mission proclaiming the novel ability to envision the world truthfully through photography, the representations of the unemployed appearing in their pages entailed tensions between surrealist romanticization of the vagabond and the impulse to document unemployment as a social reality. Some of the most celebrated photographers of their generation participated in this project of visualizing unemployment and the unemployed, contributing to a transnational repertoire of representation that has had a lasting impact upon understandings of unemployment. Ultimately, the decisive moment in the visualization of the unemployed arrived with the emergence of mass protests of the unemployed themselves. However, this success in the visual realm did not translate into success in the political sphere, as major reforms on behalf of the unemployed in France did not materialize during this period.